Efficacy of drug eluting stents in patients with and without diabetes mellitus: indirect comparison of controlled trials. Issue 5 (26th October 2005) - Stettler, C; Allemann, S; Egger, M; Windecker, S; Meier, B; Diem, P
Abstract : Objective: To examine whether polymer based coronary stents eluting sirolimus or paclitaxel are equally effective in patients with and without diabetes. Methods: Systematic review and meta-analysis by indirect comparison of randomised controlled trials comparing stents eluting sirolimus or paclitaxel with conventional bare metal stents. The overall study population and patients with and without diabetes were analysed separately by using the ratio of incidence rate ratios (RIRR). Results: The analysis was based on 10 trials (six with sirolimus, four with paclitaxel), 4513 patients (1146 patients with diabetes), 5755 years of follow up, and 2464 events. In patients without diabetes sirolimus eluting stents were superior to paclitaxel eluting stents with respect to in-stent (RIRR 0.21, 95% confidence interval (CI) 0.10 to 0.48, p < 0.001) and in-segment restenosis (RIRR 0.47, 95% CI 0.24 to 0.92, p  =  0.027), target lesion revascularisation (RIRR 0.54, 95% CI 0.30 to 0.99, p  =  0.045), and major adverse cardiac events (RIRR 0.46, 95% CI 0.26 to 0.83, p  =  0.010). In patients with diabetes the two drug eluting stents did not differ significantly in any of these end points. Meta-regression analysis showed a significant difference between patients with and without diabetes (tests for interaction for in-stent and in-segment restenosis, p  = 0.036 and p  =  0.016). Conclusion: Indirect evidence indicates that sirolimus eluting stents are superior to paclitaxel eluting stents in patients without diabetes but not in patients with diabetes.